Fabrication and memristive behavior characterization of titania thin films deposited by reactive sputtering - Shamsul, Muhamad Uzair (2013)
This paper presents the memristive behavior of sputtered titanium dioxide (TiO₂) thin films on ITO substrate. TiO₂ thin films were deposited on ITO substrate reactive sputtering method while varying the oxygen flow rate (O₂/ (O₂ + Ar) x100) from 10, 20 to 30%. TiO₂ film with 40 nm thickness was deposited between Pt and ITO substrate to form a metalinsulator-metal (MIM) structure, which is the fundamental structure of a memristive device. Current voltage measurements (I-V) of the samples were taken within the range of -5 V and 5 V. The electroforming of the I-V measurement was done by applying positive bias from 0V to 10V. It was found that the memristive behavior was less noisy after the electroforming process compared to before the electroforming and the sample deposited with 20% oxygen flow rate gave the best memristive behavior.